Organic chemistry - Fessenden, Ralph J. (Pacific Grove, California : Brooks/Cole Publishing Company, 1986)
The goal was to produce a manageable text for the one-year introductory organic chemistry course- a text designed to guide students in their studies and not simply provide a compilation of organic chemical knowledge.
1. Atoms and molecules -- 2. Orbitals and their role in covalent bonding -- 3. Structural isomerism, nomenclature and alkanes -- 4. Stereochemistry -- 5. Alkyl halides; Substitution and elimination reactions -- 6. Free-radical reactions; organometallic compounds -- 7. Alcohols, ethers, and related compounds -- 8. Spectroscopy I: infrared and nuclear magnetic resonance -- 9. Alkenes and alkynes -- 10. Aromaticity, benzene and substitute benzenes -- 11. Aldehydes and ketones -- 12. Carboxylic ketones -- 13. Derivatives of carboxylic acids -- 14. Encolates and carbanions: Building blocks for organic synthesis -- 15. Amines -- 16. Polycyclic and heterocyclic aromatic compounds -- 17. Pericyclic reactions -- 18. Carbohydrates -- 19. Amino acids and proteins -- 20. Lipids and related natural products -- 21. Spectroscopy II: Ultraviolet spectra, color and vision, mass spectra.
Keywords: CHEMISTRY -- ORGANIC